FOREIGN EXPERIENCES IN THE RELIABLE OPERATION OF BIOGAS PLANTS AND THEIR APPLICATION PROSPECTS - Karabayeva Munis Usmanovna (Next Scientists Conferences, 2025)
The development of renewable energy technologies has brought significant attention to biogas plants as a sustainable and eco-friendly solution for waste management and energy production. In many developed countries, long-term operational reliability of biogas systems has been achieved through the integration of advanced engineering solutions, strict regulatory frameworks, and community-based management approaches. The study of foreign experiences in this field demonstrates that stable biogas production depends not only on technical modernization but also on institutional support, effective maintenance practices, and continuous monitoring of microbiological processes. The lessons drawn from these international practices create valuable opportunities for adapting and applying similar approaches in other contexts, where the growing demand for renewable energy aligns with the necessity of reducing greenhouse gas emissions. The prospects of applying these models in developing countries lie in the adaptation of cost-efficient technologies, localization of operational strategies, and the establishment of educational programs aimed at enhancing technical competence in managing biogas plants.